Analisis Dampak Over-Tourism terhadap Kualitas Lingkungan dan Kehidupan Masyarakat Lokal - Rizky Ananda Pratama (Lembaga Penelitian dan Pendidikan, 2025)
Over-tourism has become a significant issue in many popular tourist destinations worldwide, where excessive visitor numbers exceed the carrying capacity of the environment and communities. This study aims to analyze the impact of over-tourism on environmental quality and the social well-being of local communities. A qualitative research design was applied, involving literature reviews and field observations in selected Indonesian tourism destinations. The findings show that over-tourism contributes to environmental degradation, including waste accumulation, air and water pollution, and biodiversity loss. Additionally, it disrupts the daily lives of local residents, leading to cultural commodification, increased cost of living, and reduced quality of social interactions. However, the study also highlights the resilience of local communities in adapting to tourism challenges, while emphasizing the need for sustainable tourism management strategies. The research concludes that policy interventions, community participation, and responsible tourism practices are crucial to mitigate the negative impacts of over-tourism. This study contributes to the broader discussion on sustainable tourism development and provides recommendations for balancing tourism growth with environmental conservation and community welfare.